Trends in the development of railway services in the current conditions of economic development - Daribekov, S.S.; Daribekova, A.S.; Ospanov, G.M. (KSU Publ., 2018)
This article examines the trends in the development of rail transport in the current conditions of economic development. The dynamics of the main indicators of the development of the railway transport in Kazakhstan and the indicators characterizing the technical equipment of the railroad in Kazakhstan are given. The analysis of the structure of cargo transportation by rail, both on the territory of the country, and on international communications is carried out. Conclusions are made on the status of these indicators. It was revealed that the structure of cargo transportation by rail is the most diversified, since not only raw materials are transported: coal, metals, ores, oil, but also food products - furniture, fertilizers, food products. The main objective is to ensure the conditions (economic and political) for an additional sustained inflow of transit cargoes to Kazakhstani routes from those countries that are currently carrying out the transportation of their goods through Kazakhstan or used these routes in the past, as well as those most attracted to Kazakhstani cargo routes.
Экономиканың осы заманғы даму жағдайында теміржол қызметін дамыту үрдістері
Тенденции развития железнодорожных услуг в современных условиях развития экономики
Keywords: railway transport; passenger turnover; freight turnover; income from rail transport; transit potential